1997
DOI: 10.1074/jbc.272.42.26734
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxyl Radicals Depolymerize Glomerular Heparan Sulfate in Vitro and in Experimental Nephrotic Syndrome

Abstract: Heparan sulfate, the polysaccharide side chain of heparan sulfate proteoglycan, is important for the permselective properties of the glomerular basement membrane. In this report, we show a role for hydroxyl radicals in heparan sulfate degradation and an enhanced glomerular basement membrane permeability. First, in enzyme-linked immunosorbent assay, exposure of coated heparan sulfate (proteoglycan) to reactive oxygen species resulted in a ؎50% decrease of binding of a monoclonal antibody against heparan sulfate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
90
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(95 citation statements)
references
References 44 publications
5
90
0
Order By: Relevance
“…The increased expression of heparanase in AN is in line with the findings in puromycin aminonucleoside nephrosis, passive Heymann nephritis, and anti-GBM nephritis (15)(16)(17)(18). The loss of glomerular HS also is in accordance with previous studies in proteinuric renal disease (7)(8)(9). Our data on a consistent association between HS and heparanase suggest that heparanase is an important factor involved in the breakdown of HS and thereby in the development of proteinuria.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…The increased expression of heparanase in AN is in line with the findings in puromycin aminonucleoside nephrosis, passive Heymann nephritis, and anti-GBM nephritis (15)(16)(17)(18). The loss of glomerular HS also is in accordance with previous studies in proteinuric renal disease (7)(8)(9). Our data on a consistent association between HS and heparanase suggest that heparanase is an important factor involved in the breakdown of HS and thereby in the development of proteinuria.…”
Section: Discussionsupporting
confidence: 80%
“…In Adriamycin nephrop-athy (AN), a model of chronic proteinuric renal damage (19), we previously reported a decrease of HS expression, which was caused partially by hydroxyl radicals (7). Furthermore, we found that RAS blockade protects against loss of HS in established AN (9).…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…HS content was determined as previously described with HS ELISA kit (Seikagaku) (36). Cells were collected and disrupted by sonication followed by centrifugation at 14,000 rpm for 10 min.…”
Section: Methodsmentioning
confidence: 99%
“…Injuries to the basement membrane can result in the release of these pro-invasive compounds. Furthermore, fragmentation of matrix proteins by free radicals or limited proteolysis can generate biologically active peptides, that is, the matrikines (Vartio 1989;Monboisse and Borel 1992;Raats et al, 1997;Duca et al, 2004). Once released, these matrikines, such as elastin peptides, can increase the expression of MMP-2, MT1-MMP and TIMP-2 in fibrosarcoma HT-1080 cells (Brassart et al, 1998).…”
mentioning
confidence: 99%